2019
DOI: 10.1002/aenm.201901685
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Efficient and Stable CsPbI3 Perovskite Solar Cells through Cation Exchange Process

Abstract: and rapid increase in power conversion efficiency (PCE) to 25.2% most recently reported. [1] Inorganic lead halide perov skites have also attracted attention with the number of research work and demon strated efficiencies constantly on the rise [2] due to the elimination of organic cat ions and tolerance to higher processing temperatures.Among inorganic halide perovskites, CsPbI 3 has gained popularity due to the optical bandgap of 1.72 eV, which is suit able for tandem devices combining with either silicon or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 29 publications
4
84
0
Order By: Relevance
“…In addition, no any details including the adopted model, fitting parameters, comparison between the ellipsometric data and the fitting results, as well as sample stability were given . Because the PCE of CsPbI 3 perovskite solar cells is progressing fast with latest report of up to 18%, the experimental determination of the optical constants of CsPbI 3 perovskite thin films is never as urgent as now.…”
Section: The Extracted Parameters From the Best Fitting To Ellipsometmentioning
confidence: 99%
“…In addition, no any details including the adopted model, fitting parameters, comparison between the ellipsometric data and the fitting results, as well as sample stability were given . Because the PCE of CsPbI 3 perovskite solar cells is progressing fast with latest report of up to 18%, the experimental determination of the optical constants of CsPbI 3 perovskite thin films is never as urgent as now.…”
Section: The Extracted Parameters From the Best Fitting To Ellipsometmentioning
confidence: 99%
“…Despite the non-ideal tolerance factor of all-inorganic halide perovskites, there are successful attempts towards increasing the stability. [32,[81][82][83][84][85][86] One intriguing study revealed the correlation between formation conditions and improved stability: solution deposition on clamped substrates enabled a stable α-CsPbI 3 phase at room temperature. [32] Their in situ GIWAXS analysis of the crystal distortions and strain-driven texture formation showed that the detrimental α-to δ-phase transformation could be suppressed when cooling the thin film to room temperature.…”
Section: Temperaturementioning
confidence: 99%
“…For the PSC with a TiO 2 /ZnO bilayer ETL, its PCE is strongly increased to 21.06% by the increased doping concentration in the ZnO layer because of the enlarged FF of approximately 74.07%. These values are far higher than not only those of the PSC with a TiO 2 / ZnO bilayer ETL and low doping concentration and the PSC with a single-layer ZnO ETL and high doping concentration but also those of previous reports [16,28,[60][61][62][63][64][65] as listed in Table 2 and shown in Fig. 8b.…”
Section: Resultsmentioning
confidence: 50%
“…Hence, the increased doping concentration does not affect the FF and PCE of the PSC with a PCBM/ZnO bilayer ETL. Moreover, although the improved performances of the PSC with a PCBM/ZnO bilayer ETL are superior to those of other CsPbI 3 -based PSCs [16,28,[60][61][62][63][64][65], they are lower than those of the PSC with a TiO 2 /ZnO bilayer ETL, as shown in Fig. 8b.…”
Section: Resultsmentioning
confidence: 84%